The Influence of Audit Materiality, Compliance with Audit Standards (SA), Material Misstatement on Sustainability Performance and Audit Opinion with Fairness Principle as Moderating Variable: (On Mining Companies Listed on the IDX in 2019-2023) - Vivi Armadhani; Tri Ratnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of audit materiality, compliance with audit standards (SA), and material misstatements on sustainability performance and audit opinion, with the principle of fairness as a moderating variable in mining companies listed on the Indonesia Stock Exchange ( IDX) for the 2019-2023 period. This research was conducted with a quantitative approach, using secondary data in the form of financial reports, sustainability reports, and independent audit reports. The results showed that compliance with audit standards has a significant effect on sustainability performance and audit opinion, while audit materiality and material misstatement do not have a significant effect directly on these two variables. In addition, the principle of fairness as a moderating variable does not strengthen the relationship between sustainability performance and audit opinion. These findings suggest that mining companies need to improve transparency and compliance with audit standards to support sustainability and obtain better audit opinions. This research provides a theoretical contribution to the study of sustainability accounting as well as practical guidance for auditors and company management in improving the quality of financial reporting and sustainability.